Multi-patient monitoring system using a reliable wireless sensor protocol - Koh, Kim Ho (2009)
Patient monitoring system is a monitoring system for providing Continuous health monitoring of a patient. The aim is to collect and store important parameters of patient during critical period. In addition, it also helps to improve patient care and make early detection, of medical emergencies. Previous monitoring systems are using wired system which can be seen right next to the patient. Now with wireless, nurses can monitor patients in distance. Next, too much of wire will easily cause accident. In addition, patient movements will also be limited. Therefore, wireless eliminates unsightly cables and patients can freely move around. Besides, wired system will cause the transmission delay problem. But, with wireless technology, the delay problem will be reduced.